Analyzing The Total Resistance and Wave Pattern of Modification Hull Form Design Catamaran Fishing Vessel - Rizqi Fitri Naryanto; Muhammad Yusuf Wibowo; Aldias Bahatmaka; Muhammad Hafiz Izzuddin; Lanang Puspa Buana; Rafif Dimas Pratama; Fiqri Fadillah Fahmi; Andi Abdullah Ghyferi (National Research and Innovation Agency (BRIN Publishing), 2024)
Indonesia is located between the Pacific Ocean and the Indian Ocean. In addition, Indonesia is a maritime country, with data stating that Indonesia’s sea proportion is 64.97% of the total territory of Indonesia. Diverse marine resources exist in Indonesia, and the country produces 8.02 million tons of fish annually. In Indonesia, the traditional fishing vessel serves as both a mode of transportation and an element of livelihood. It was built using techniques passed down from generation to generation. Therefore, it is necessary to investigate the fishing vessels in order to determine their resistance profile and wave pattern. This analysis is done to take the catamaran-hull fishing vessel design into reference. The performance of ship design can be quickly predicted using a computational approach. The Slender Body approach and Savitsky's mathematical model are used to investigate the resistance analysis. The primary method used to describe the efficacy of the methodology is study comparison. This research will discuss the three variations of the fishing vessel design.